Are higher education institutions in Europe preparing students for IPSAS?. Issue 2 (24th July 2019) - Adam, Berit; Brusca, Isabel; Caperchione, Eugenio; Heiling, Jens; Jorge, Susana Margarida F.; Manes Rossi, Francesca
Abstract : Purpose: The purpose of this paper is to analyze whether higher education institutions (HEIs) in EU Member States are aware of the relevance of the ongoing reforms in public sector accounting (PSA) and the need to prepare their students to become expert professionals in that area. It particularly assesses whether these organizations currently provide, or will provide in the near future, education on International Public Sector Accounting Standard (IPSAS)/EPSAS, so that a sufficient number of graduates will be ready to match the foreseeable demand for experts in IPSAS/EPSAS. Design/methodology/approach: Adopting a purposive sample, the paper compares the situation in four EU countries (Germany, Italy, Portugal and Spain). Data have been obtained through a questionnaire provided to selected professors in relevant HEIs in the selected countries. Findings: HEIs are giving only limited room to PSA and financial management, with differences in terms of program offerings and coverage of topics among the four countries. Furthermore, in most cases, the programs are adapted to the national budgetary and accounting standards and courses are seldom focused on the IPSASs. Originality/value: The paper contributes to the literature on PSA harmonization, through an innovative analysis of PSA and financial management teaching, both at national and international levels.